Phage therapy in the destruction of Pseudomonas aeruginosa biofilms in urine - Martinho, Inês Mónica (2023)
Pseudomonas aeruginosa stands out as one of the most challenging pathogens in healthcare settings, namely because of its ability to resist several classes of antibiotics, form biofilms and cause several types of infections such as urinary tract infections. In this sense, new alternatives to conventional antimicrobials are needed. Phage therapy emerges as a promising alternative to antibiotics. This therapy involves the use of bacteriophages (also called phages), viruses that specifically infect and kill bacteria. In this study, 3 different phages (phPA-G, phPA-Intesti and phPA-Pyo) were used, alone or in a cocktail, to inactivate a P. aeruginosa strain. Planktonic bacteria assays were carried out in Tryptic Soy Broth (TSB), at 37 °C at multiplicity of infection (MOI, the ratio between the number of phages and bacteria) of 1, 10 and 100. The most effective phage against the planktonic bacteria was then selected to destroy P. aeruginosa biofilms, and to test the combined action of the phage and an antibiotic (ciprofloxacin). The results demonstrated that the most effective phage against the planktonic bacteria was phPA-Intesti, with a maximum reduction of around 4 log colony forming units (CFU)/mL, after 8 h (MOI of 1). On the P. aeruginosa biofilm assays, phPA-Intesti demonstrated to be more efficient than ciprofloxacin, with a bacterial biofilm reduction of 5 log CFU/mL, after 4 h. The ciprofloxacin caused a bacterial biofilm reduction of 4 log CFU/mL, after 4 h. The combination of phage and antibiotic did not improve the biofilm inactivation. The phage phPA-Intesti has been shown to be effective against P. aeruginosa biofilms with even better results than those obtained with the antibiotic. In a world, where antibiotic resistance is a serious public health problem, phage therapy reappears as a viable alternative to antibiotics.